Congenital heart disease in Down Syndrome focusing on atrioventricular septal defect: literature review (Research, Society and Development, 2022)
Down Syndrome is the most frequent aneuploidy in the world, with an incidence of 1 in every 700 live births. The most common characteristics of this population are intellectual disability, short stature, typical facial features and congenital malformations such as the atrioventricular septal defect, which is the most frequent. It occurs due to the poor development of the atrioventricular endocardial cushions, which is linked to the CRELD1 gene from the amplification of the gene dosage and the gene mutation, or also due to the malformation of the dorsal mesenchymal protrusion, from the formation of the atrioventricular junction. The diagnosis of this pathology becomes late because symptoms may be absent during the first days of life, leading to complications such as heart failure, pneumonia, cardiac arrhythmias or pulmonary hypertension and in some cases, only surgery is able to solve the problem. The aim of this study was to analyze the atrioventricular septal defect in people with Down Syndrome and congenital heart disease from the literature review.